Predicting ventricular arrhythmias in cardiac resynchronization therapy: The impact of persistent electrical dyssynchrony - Karaca, Oğuz; Güneş, Hacı Murat; Omaygenç, Mehmet Onur; Çakal, Beytullah; Çakal Deniz, Sinem; Demir, Gültekin Günhan; Kızılırmak, Filiz; Gökdeniz, Tayyar; Barutçu, İrfan; Boztosun, Bilal; Kılıçaslan, Fethi (Wiley, 2016)
BackgroundAlthough response to cardiac resynchronization therapy (CRT) has been conventionally assessed with left ventricular volume reduction, ventricular arrhythmias (ventricular tachycardia/ventricular fibrillation [VT/VF]) are of critical importance associated with unfavorable outcomes even in the superresponders to therapy. We evaluated the predictors of VT/VF and the association of residual dyssynchrony during follow-up. MethodsNinety-five patients receiving CRT were followed-up for 9 3 months. Post-CRT dyssynchrony was defined as a prolonged QRS duration (QRSd) for persistent electrical dyssynchrony (ED), and a Yu index 33 ms for persistent mechanical dyssynchrony. The first VT/VF episode, including nonsustained VT detected on device interrogation and/or appropriate antitachycardia pacing or shock for VT/VF, were the end points of the study. ResultsForty-five patients who reached the study end points had significantly lower mean QRS (baseline QRSd - post-CRT QRSd) values than those without VT/VF (-20.8 +/- 28.9 ms vs -6.6 +/- 30.7 ms, P = 0.022). Both the baseline and post-CRT QRSds, along with the Yu index values, were not different in two groups. Patients with VT/VF were statistically more likely to have persistent ED (38% vs 9%, P = 0.021). Kaplan-Meier curves showed that a negative QRS was associated with a higher incidence of VT/VF during follow-up (P = 0.016). A multivariate Cox model revealed that QRS prolongation was an independent predictor of VT/VF after CRT (P = 0.029). ConclusionsA negative QRS, also called persistent ED, is associated with VT/VF. Narrowest possible QRSd might be a reliable goal of both implantation and optimization of devices to reduce arrhythmic events after CRT.
WOS: 000383572900008
PubMed ID: 27333978
Keywords: Cardiac Resynchronization Therapy; QRS Duration; Ventricular Arrhythmia; Electrical Dyssynchrony; Mechanical Dyssynchrony